Foreign Language Learners Acquire L2 Phonetic Detail: Goose and Foot Fronting in Non-Native English - Šimáčková, Šárka; Podlipský, Václav Jonáš (Research in Language, 2017)
Whether late learners discern fine phonetic detail in second-language (L2) input, form new phonetic categories, and realize them accurately remains a relevant question in L2 phonology, especially for foreign-language (FL) learning characterized by limited exposure to interactional native input. Our study focuses on advanced Czech learners’ production of the L2 English vowels GOOSE and FOOT. While English /u/ and /ʊ/ have been undergoing fronting, their Czech equivalents, /uː/ and /u/, are fully back. We show that although the spectral differentiation of /u/-/ʊ/ is smaller in the learners’ than in native speech, the vowels being contrasted primarily in length, even FL learners can shift their L2 sound categories towards native-like targets, or in this case, produce English /u/-/ʊ/ as fronted.